‘Makhosi a via (Chiefs Commit Ritual Murder)’ – Why ritual murders in Southern Africa should be seen as meaningful violence (and not senseless) - de Jong, Wiebe (Afrika Focus, 2015)
Ritual or muti murder involves the practice wherein parts of the victim’s body are removed, usually while the victim is alive, for the purpose of making medicine to politically or economically strengthen those who use it. In this article it is argued that, in order to understand this ritual, we should focus on the cultural dynamics of ritual murder and perceive it as meaningful violence. There is, however, a growing tendency to understand ritual murders in rational, utilitarian terms, which has the inadvertent effect of missing the ‘thick description’ that may provide insight into the meaning of ritual murders and the question of why it persists in present-day society. As will be explained, with such an approach ritual murders can only appear as senseless. It cuts off the research at the point where it should actually start: with questions of meaning. By presenting his- torical and ethnographic evidence from South Africa, it is shown that ritual murders were once an accepted means of strengthening the king or chief, and as such, of preserving the whole society. It is argued that in the present day, people still practise ritual murders to politically or economically strengthen themselves, but that this point is neglected in public debate and the media. By focusing on two recent ritual murder cases, it is shown that this neglect has severe consequences for think- ing about, and dealing with ritual murders.